On the augmented reproducibility in measurements on 3D orthodontic digital dental models and the definition of feature points - Jacquet Wolfgang; Nyssen Edgard; Ibel Gabriele; Vannet Bart Vande (Australasian Orthodontic Journal, 2013)
Objective: The objective of this study was to explore digital measurement methodology on 3-dimensional (3D) dental models. Standardised manipulation and practices have lead to reliable measurements on plaster casts. Identifying landmarks on digital models or digitised plaster casts is fundamentally different from actual measurements. Three-dimensional models are represented on flat screens and landmarks are individually indentified. A procedure is proposed that resolves the deficiencies associated with a 2-dimensional (2D) display through an appropriate model representation and through local optimisation.